Student perceptions of cheating behavior during learning evaluation: A case study of Indonesian students - Ika Kana Trisnawati; Yuniarti Yuniarti (Proceedings of AICS - Social Sciences, 2017)
Cheating has become a deep-rooted problem in the academic settings. There are various reasons which cause cheating to remain undiminished despite attempts made to reduce the frequency of cheating in academia. This study focuses on the student perceptions of cheating behavior, the cheating practices done by the students, and the factors influencing the students’ cheating behavior during learning evaluation. The participants were 43 students of the Department of English Education, Faculty of Islamic Studies, University of Muhammadiyah Aceh. These respondents were asked to complete a survey questionnaire consisting of demographic questions and cheating-related questions from which data were compiled and analyzed using the SPSS. Findings showed that the students were aware that cheating was against moral values. However, as much as 84% of the students admitted to having done cheating during exam or when doing assignments. The most common cheating practices included asking for and swapping answers with friends during exam, copying materials from books/internet and submitting them, and collaborating with friends when doing assignments that meant to be completed individually. There were external and internal factors contributing to these cheating practices. The external ones were highly difficult exam, too many assignments, not enough time in completing the assignments, and helping friends, among others. And, the internal factors were related to being afraid of getting low scores and failing in exams, and the motivation to have a high score. On the other hand, about 16% of the students claimed to never cheat due to religious/moral reasons, pride in their own ability, and fear of getting punishment. The results of the study are hoped to give valuable input on the policy of academic cheating in Indonesian higher education.